Análise da microdureza dos agentes cimentantes utilizados para cimentação de pinos de fibra submetidos à termociclagem - Kian, Adriano Takashi [UNESP] (2011)
The aim of this study was to analyze the microhardness of resin cements used in cementing glass fiber posts in bovine incisors. The microhardness was analyzed in cervical thirds, middle and apical before and after thermocycling process. After extraction, the bovine incisors were stored in aqueous 2% formaldehyde, pH 7 for 30 days, then scalled with periodontal curettes number 11-12 and cleaned with bicarbonate jet and water. After, the teeth were stored in 0.9% saline and performed a selection of teeth with straight roots and similar forms. The teeth were sectioned obtaining 17mm standardized roots, in order to obtain similar dimensions to each other. We discarded the teeth that had root canal width greater than the Largo drill No. 5. After selection, the teeth were obturated and prepared their canals at a depth of 12mm. After desobturation, the roots and glass fiber posts were prepared for adhesive cementation according to the indication of the manufacturers of cements. After cementation of fiber posts, microhardness reading was carried out with the Microhardness Shimadzu Micro Hardness Tester HMV-2000. After initial reading, the samples were placed in a thermocycler and subjected to 2,000 cycles and a new microhardness reading. The data collected were subjected to analysis of variance (ANOVA) and Tukey's test, where it was observed that there was statistical difference between the microhardness of resin cements, however, there was statistical difference of microhardness before and after thermocycling only in group U-100. The Multilink resin cement showed the lowest levels of average hardness, however, was also the one that had the lowest change after 2000 cycles of thermocycling. Moreover, the resin cement U-100 was the one that had the highest average microhardness both before and after thermocycling test